Acute myocardial infarction following carbon monoxide poisoning - Altay, Servet; Bozbay, Mehmet; Dedemoğlu, Mehmet; Ayhan, Erkan; Eren, Mehmet; Çakmak, Hüseyin Altuğ (Cerrahpaşa Medical Journal, 2013)
Carbonmonoxide (CO) exposure is one of the most common reasons of poisoning death. Carbon monoxide is a colorless, odorless, tasteless and nonirritant gas. Clinical manifestation usually involves central nervous and cardiovascular systems, because brain and heart are very sensitive to hypoxia. CO has a higher affinity for hemoglobin than does oxygen, it attaches to the hemoglobin of the red blood cells and blocks their capacity to carry oxygen. As a result, elevated blood concentration of CO leads to reduced tissue oxygen delivery. Myocardial infarction pathogenesis during CO intoxication is complex. Widespread tissue hypoxia and increased thrombotic tendency have an important role. Such cardiac involvement may occur promptly after CO exposure, or it may be delayed for several days. We have a 69 years old female who had an acute myocardical infarction after the CO exposure. We think that infarction is precipitated by CO exposure in our patient who had coronary artery disease before.